Literary Hermeneutics in The Context of Natiosophic Ideas - Kolkutina, Viktoriia; Syniavska, Lesya; Pohrebennyk, Volodymyr; Kornisheva, Tetiana; Iaremchuk, Natalia (Տիգրան Մեծ)
The article looks at the literary hermeneutics in the context of natiosophic ideas by H.-G. Gadamer, S. During, M. Heidegger, E. Smith, E. Said, D. Dontsov. It investigates the freedomcentred nature of nationalism, discovers new meanings of the concept “cultural nationalism”, as well as the key concepts of the natiosophic aesthetics. The research outlines the natiosophic specifics of the interpretation system through the comprehension of the various concepts. It sums up that nationalist interpretation is essentially natiologic (natiosophic). However, it is also literary, with the coherent semantic level of cognition. The evaluation here dominates over the formal-and-aesthetic level, which is quite common for such type of experience. Culturological aesthetics in the ontological existential dimension is deeply rooted in the nation’s being. It has a pronounced nation-creating nature, targeted at establishing a national identity that is grounded on the national idea. Under the colonial oppression, it finds its expression in the interpretation of the fiction texts as a writer’s spiritual-and-worldview systems of values.
Keywords: Philosophy